(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes the effectiveness of using artificial intelligence technologies in Russian language lessons. The role of artificial intelligence tools in the language learning process, especially in the development of students’ speaking and writing skills, is discussed. The article considers the advantages of using artificial intelligence in the process of learning the Russian language, such as automatic translation, detection of grammar and spelling errors, creation of individual educational approaches, and the effectiveness of interactive lessons. In addition, new methods and techniques for conducting lessons with the help of technologies are presented. The article expresses its views on the prospects for using artificial intelligence tools in learning the Russian language and its role in the field of education.